Does the Microbiota Composition Influence the Efficacy of Colorectal Cancer Immunotherapy? - Lin, Yan; Kong, De-Xia; Zhang, You-Ni (Frontiers in Oncology, 2022)
Colorectal cancer (CRC) is the second most common malignancy globally, and many people with CRC suffer the fate of death. Due to the importance of CRC and its negative impact on communities, treatment strategies to control it or increase patient survival are being studied. Traditional therapies, including surgery and chemotherapy, have been used to treat CRC patients. However, with the advancement of science, we are witnessing the emergence of novel therapeutic approaches such as immunotherapy for CRC treatment, which have had relatively satisfactory clinical outcomes. Evidence shows that gastrointestinal (GI) microbiota, including various bacterial species, viruses, and fungi, can affect various biological events, regulate the immune system, and even treat diseases like human malignancies. CRC has recently shown that the gut microorganism pattern can alter both anti-tumor and pro-tumor responses, as well as cancer immunotherapy. Of course, this is also true of traditional therapies because it has been revealed that gut microbiota can also reduce the side effects of chemotherapy. Therefore, this review summarized the effects of gut microbiota on CRC immunotherapy.